2017
DOI: 10.1007/s11356-017-0700-0
|View full text |Cite
|
Sign up to set email alerts
|

Malathion-induced spermatozoal oxidative damage and alterations in sperm quality of endangered trout Salmo coruhensis

Abstract: The use of pesticides has been increased along with increasing the farming activities and has caused environmental impacts deleteriously. In particular, non-target organisms including fish can be affected by toxic effects of pesticides. Therefore, the impacts of malathion (MTN) on oxidative stress and sperm quality were investigated in vitro. The MTN concentrations used on this study were 0 (control), 75, 100, and 125 μg/L. Lipid peroxidation (MDA), non-enzymatic (GSH), and enzymatic (SOD, GSH-Px, and CAT) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Corroborating our results, Kocabaş et al 48 showed that sperm cells exposed to malathion in an in vitro model (75, 100, and 125 μg/L) showed increased antioxidant enzyme CAT activity and reduced SOD activity, even though MDA GSH levels were unaltered. Thus, we confirmed that malathion alters the oxidative status of sperm cells, regardless of the model used.…”
Section: Discussionsupporting
confidence: 90%
“…Corroborating our results, Kocabaş et al 48 showed that sperm cells exposed to malathion in an in vitro model (75, 100, and 125 μg/L) showed increased antioxidant enzyme CAT activity and reduced SOD activity, even though MDA GSH levels were unaltered. Thus, we confirmed that malathion alters the oxidative status of sperm cells, regardless of the model used.…”
Section: Discussionsupporting
confidence: 90%
“…[27][28][29][30][31] Pesticides display toxic effects causing oxidative stress and affecting antioxidants statues including enzymatic elements such as superoxide dismutase (SOD; EC 1.15.1.1), catalase (CAT; EC 1.11.1.21), glutathione peroxidase (GPx; EC 1.11.1.9), glutathione reductase (GR; EC 1.6.4.2), glutathione S-transferase (GST; EC 2.5.1.18), or non-enzymatic such as glutathione (GSH), ascorbic acid, tocopherol are being studied as potential biomarkers in environmental risk assessment together with lipid peroxidation products such as thiobarbituric reactive species (TBARS). [32][33][34][35][36] GSH is the most abundant intracellular small molecule thiol and a water-soluble tripeptide composed of the amino acids glutamine, cysteine, and glycine. As an important antioxidant, GSH plays a role in the detoxification of a variety of electrophilic compounds and peroxides via catalysis by GST and GPx.…”
Section: Introductionmentioning
confidence: 99%